Upaya Meningkatkan Hasil Belajar Peserta Didik di Kelas V-A UPT SD Negeri 060924 Medan Amplas Melalui Pembelajaran Menggunakan Multimedia Berbasis Wordwall pada Materi Sistem Pernapasan Manusia - Simamora, Ester Agnes; Prawiyata, Yugi Diraga; Asnawi, Asnawi; Tanjung, Cici Febi Putri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve the learning outcomes of students in the subject of Natural and Social Sciences on the topic of the Human Respiratory System by using Wordwall learning media for fifth-grade students in class V-A at SD Negeri 060924 Medan Amplas. This type of research is a Classroom Action Research (CAR) with a total of 20 students in class V-A who face challenges in effectively understanding the concepts of the human respiratory system. To collect data for this study, the author employed pretest and posttest techniques. The instrument used was a test designed to measure students' knowledge. Data analysis was conducted using both qualitative and quantitative methods. The results of the research in cycle 1 showed that only 8 out of 20 students achieved the Minimum Completeness Criteria of 75. The average score obtained was 65, with a completeness percentage of 40%. In contrast, the results of the research in cycle II indicated an improvement in students' learning outcomes, with 18 out of 20 students achieving completeness, and the overall average score was 84.25, with a completeness percentage of 90%. Based on this research, the learning activities designed using Wordwall media helped students better understand the concept of the human respiratory system, leading to an increase in students' learning outcomes.